2015
DOI: 10.14444/2016
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Comparison of Lateral Lumbar Interbody Fusion Versus Traditional Fusion Approaches: Analysis of Sagittal Contour Change

Abstract: Background Lateral approach to lumbar fusion has been gaining popularity in recent years. With increasing awareness of the significance of sagittal balance restoration in spinal surgery, it is important to investigate the potential of this relatively new approach in correcting sagittal deformities in comparison to conventional approaches. The aim of this study was to evaluate sagittal contour changes seen in lateral lumbar interbody fusion and compare them with radiographic changes in traditional approaches to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
33
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 29 publications
8
33
0
2
Order By: Relevance
“…ALIF, TLIF, PLIF, and PLF) (e.g., greater end plate/disc removal, restoration of sagittal balance and/or lordosis, but early cage settling) [ Table 1 ]. [ 12 22 26 27 ] Tatsumi et al . found that for four fusions (ALIF, PLIF, TLIF, and XLIF) performed in 8 cadavers (24 disc spaces and 48 end plates from L2-L5), MIS XLIF provided the most extensive end plate preparation (58.3%) and disc removal (90%), whereas less disc was removed for the other constructs (e.g.…”
Section: Pros and Cons Of Xlif: X-ray/computed Tomography (Ct) And Bimentioning
confidence: 99%
See 2 more Smart Citations
“…ALIF, TLIF, PLIF, and PLF) (e.g., greater end plate/disc removal, restoration of sagittal balance and/or lordosis, but early cage settling) [ Table 1 ]. [ 12 22 26 27 ] Tatsumi et al . found that for four fusions (ALIF, PLIF, TLIF, and XLIF) performed in 8 cadavers (24 disc spaces and 48 end plates from L2-L5), MIS XLIF provided the most extensive end plate preparation (58.3%) and disc removal (90%), whereas less disc was removed for the other constructs (e.g.…”
Section: Pros and Cons Of Xlif: X-ray/computed Tomography (Ct) And Bimentioning
confidence: 99%
“…noted on standing pre and 6-week postoperative X-rays (147 patients; 212 levels fused), that all constructs demonstrated comparable improvement in sagittal balance, but that ALIF provided better segmental/general correction. [ 22 ] For Tohmeh et al ., 140 patients undergoing MIS XLIF/pedicle screw fixation at 223 levels (followed for 15.5 postoperative months), despite increases in overall lordosis (4.0 to 8.1) and segmental lordosis (10.7 to 13.7), cage settling (e.g. >1 mm or more) occurred in 20% of patients immediately postoperatively and in 62% of the patients within 1 postoperative year.…”
Section: Pros and Cons Of Xlif: X-ray/computed Tomography (Ct) And Bimentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with ASD and mild to moderate global sagittal imbalance (sagittal vertical axis [SVA] less than 10 cm), 26 surgical strategies are widely varied according to surgeon preference for interbody fusion, adaptation of minimally invasive surgical technique, and type of deformity. 14,23,27 In an attempt to decrease blood loss, minimize softtissue dissection, and improve recovery times after ASD operations, minimally invasive surgical approaches have gained popularity in this arena. Although concerns have been raised regarding the ability of these approaches to correct sagittal plane deformity, the evolution of instrumentation for minimally invasive surgeries has broadened their applicability.…”
mentioning
confidence: 99%
“…Finally, the aim of this surgical correction was to correct spondylolisthesis; therefore, the reduction in the distance of slippage and restoration of HOD was necessary. The TLIF procedure has been widely accepted since 1998 and is able to improve HOD effectively (27,30,37). In the present study, unlike SD, HOD demonstrated a significant correlation with some of the sagittal spinopelvic parameters.…”
Section: Statisticsmentioning
confidence: 41%